Response Surface Estimates of the Cross-Sectionally Augmented IPS Tests for Panel Unit Roots (2013)
This paper estimates response surface coefficients for a large range of quantiles of the cross-sectionally augmented IPS (CIPS) test of Pesaran (2007), for different specifications of the deterministic components. An Excel programme is available to calculate the P value associated with a CIPS test statistic. © 2011 Springer Science+Business Media, LLC.